The bond behavior of steel reinforced recycled concrete under cyclic reversed load. (1st December 2021) - Xue, Jianyang; Li, Hechao; Ren, Rui; Zhang, Xin
Highlights: Use the electromagnetic slip sensor to measure the slip. The slip appears on both ends of steel reinforced recycled concrete firstly. Substantial degradation of bond capacity took place during cyclic loading. The bond strength decreases with recycled concrete aggregate percentage increasing. Abstract: In order to investigate the cyclic bond behavior between H-shaped steel and recycled concrete, thirteen cyclic reversed push-out tests and one monotonic push-out test were carried out. The main parameters of the tests were recycled concrete aggregate (RCA) replacement percentage, thickness of concrete cover, stirrup ratio, recycled concrete strength and loading scheme. The experimental results indicate that the pinch effect on the hysteresis curves of load-slip is remarkable. The envelope curves can be divided into four stages: minimal slip stage, slip development stage, falling stage and residual stage. The bond stress of steel reinforced recycled concrete (SRRC) under cyclic reversed load declines by 40%∼50% comparing to SRRC under monotonic push-out load. Slip appears on both ends of the specimens firstly under cyclic reversed load. The influence of the main factors on the cyclic bond stress is analyzed. The energy dissipation mainly occurs in the falling stage and residual stage.